Implementasi Pelayanan Publik Berbasis Digital dalam Dunia Pendidikan - Dewi Lailatul Kusna; Imro'atul Fauziyah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The rapid growth of digital technology has brought substantial changes to the delivery of public services in the education sector. This study examines the adoption of digital systems in educational services, focusing on their key characteristics, implementation patterns, and governing principles. Employing a literature review approach and content analysis, this paper synthesizes findings from scholarly sources and relevant studies on the digital transformation of educational services in Indonesia. The results indicate that the integration of information technology not only streamlines administrative processes and expands access to services but also enhances transparency, accountability, and data security within educational management. Various digital platforms—including academic information systems, online administrative services, complaint portals, and educational analytics tools—contribute to improving governance effectiveness and service quality. The success of digital service implementation is strongly influenced by infrastructure readiness, human resource capacity, regulatory support, and user participation. Overall, the digitalization of public services in education serves as a vital strategy for fostering more inclusive, efficient, and responsive educational services. Keywords: Digital education, digital public services, educational governance, service quality, information technology